Pengaruh Pemikiran Abu Raihan Al-Biruni terhadap Perkembangan Ilmu Falak - Jannah, Elly Uzlifatul (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
The research paper "The Influence of Abu Raihan Al-Biruni's Thoughts on the Development of Astronomy" delves into the profound impact of Abu Raihan al-Biruni's ideas on the field of astronomy. It conclusively demonstrates that al-Biruni's astronomical insights were remarkably advanced for his era, often surpassing the comprehension of his contemporaries. His meticulous observations and precise data align closely with modern astronomical research standards. Al-Biruni's pivotal contributions to astronomy include determining the declination of the Sun and zenith movement, precise calculations of latitude and longitude, elucidating solar eclipse phenomena, and employing spherical trigonometry to calculate the Earth's circumference and diameter. Moreover, he adeptly used spherical triangle knowledge to calculate the direction of the Qibla.